Analysis of perfomance indicators that discriminate winning and losing teams in new Basketball Brazil - Prochnow, R. A.; Reale, V. M. C.; Santos, Y. Y. S; Monezi, L. A.; Mercadante, L. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of this study was to verify which are the technical indicators that differentiate the winning teams from losers in the New Basketball Brazil (NBB) and in each of the seven seasons analysed. The specific objective was to verify in the discriminant analysis the effect of normalizing the technical indicators by the number of attacks. The sample consisted of 1912 matches of seasons between 2008 and 2015 of the NBB. The successful rate of the discriminant function was closely to 82%, without substantial difference between the analysis with the normalized and non-normalized technical indicators. The indicators that discriminate the winner team from loser in were defensive rebounds and assists. Other indicators related to the two and three points shoot were found in different seasons.